Comparative Literature Study of Bligo Fruit Extract (Benincasa hispida (Thunb) Cogn) and Bitter Melon (Momordica charantia L.) Extract on the Minimum Inhibition of Salmonella typhi Bacteria - Mei Rizqi Putri Afifah; Noer Kumala Indahsari (Fakultas Kedokteran Universitas Lambung Mangkurat, 2021)
Abstract: Salmonella typhi is a gram-negative bacteria species that causes typhoid fever. Salmonella typhi is sensitive to antibiotics such as amoxicillin, chloramphenicol, ciprofloxacin, and cotrimoxazole. However, there has been some increase in antibiotic resistance, so there is a need for new antibacterials that do not have a resistance effect to treat infection. Bligo fruit (Benincasa hispida (Thunb) Cogn) and bitter melon (Momordica charantia L.) contain saponins, tannins, flavonoids, alkaloids, and triterpenoids which have antibacterial power. The purpose of this study was to compare the effectiveness of the bligo fruit extract (Benincasa hispida (Thunb) Cogn) and bitter melon extract (Momordica charantia L.) on the minimum inhibition of Salmonella typhi bacteria. The method used is narrative literature review. The results of the journal study showed that the extract of bitter melon (Momordica charantia L.) was more effective in inhibiting Salmonella typhi bacteria than the extract of bligo (Benincasa hispida (Thunb) Cogn) with a minimum inhibitory power at a concentration of 20%, namely 8.5 mm. Keywords: Bligo Fruit (Benincasa hispida (Thunb) Cogn), Bitter Melon (Momordica charantia L.), Salmonella typhi.